1995
DOI: 10.1016/1074-5521(95)90091-8
|View full text |Cite
|
Sign up to set email alerts
|

Using evolutionary changes to achieve species-specific inhibition of enzyme action — studies with triosephosphate isomerase

Abstract: Cys14 of trypanosomal TIM is a non-conserved amino acid whose alteration leads to loss of enzyme structure and function. TIMs that have a cysteine residue at position 14 could be selectively inhibited by MMTS. This approach may offer an alternative route to species-specific enzyme inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
67
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 62 publications
4
67
0
1
Order By: Relevance
“…Enzymatic activity assays. Enzymatic activity was determined following the conversion of glyceraldehyde 3-phosphate into dihydroxyacetone phosphate [7]. The decrease in absorbance at 340 nm was followed in a multicell Cary spectrophotometer at 25 °C.…”
Section: Inhibition Of Tctimmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzymatic activity assays. Enzymatic activity was determined following the conversion of glyceraldehyde 3-phosphate into dihydroxyacetone phosphate [7]. The decrease in absorbance at 340 nm was followed in a multicell Cary spectrophotometer at 25 °C.…”
Section: Inhibition Of Tctimmentioning
confidence: 99%
“…TcTIM is considered a potential target for anti-trypanosomal drugs [7][8][9]. This enzyme is involved in the glycolysis pathway of the parasite.…”
Section: Introductionmentioning
confidence: 99%
“…This proved to be the case. Following the idea that from measurements of the effect of a given reagent in homologous enzymes, it is possible to gain insight or determine the residue that is modified [6], we found that among triosephosphate isomerases that lack Cysl4, only those that have a Cys in position 217 are inhibited by a thiosulfonate that produces phenyl disulfides. Thus, the results illustrate that nonconserved residues can be used to find or produce species-specific inhibitors of homologous enzymes that exhibit a high level of selectivity.…”
mentioning
confidence: 99%
“…In more general terms, we studied whether various non-conserved residues in triosephosphate isomerase could represent potential targets for selective inhibition of homologous enzymes. Our leads in these studies were that some specific and non-specific sulfhydryl reagents inhibit the activity of triosephosphate isomerase from various species to different extents and that in rabbit triosephos-phate isomerase which has five Cys but lacks Cysl4, MeS0,-SMe produces a small inhibiting effect [6]. We therefore studied whether a higher inhibition could be produced in rabbit triosephosphate isomerase by larger derivatizing groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation